PENGARUH TAX AVOIDANCE TERHADAP COST OF DEBT DENGAN TAX RISK SEBAGAI VARIABEL MODERASI (Bukti Empiris pada Perusahaan Non-Finansial yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Dongan Basar Kristianto Manalu; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of tax avoidance on the cost of debt, with tax risk as a moderating variable, in companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The cost of debt, serving as the dependent Variable, is measured by the ratio of interest expense to total short-term and long-term liabilities. Tax avoidance is measured using the effective tax rate (ETR), while Tax risk is calculated based on the standard deviation of ETR over two consecutive years. To ensure a more comprehensive analysis, control Variables such as firm size (SIZE), leverage (LEV), and liquidity (LIQ) are included. This research employs a quantitative approach by analyzing secondary data from 138 purposively sampled companies, resulting in a total of 414 observations over three years. Data analysis was conducted through multiple regression and moderated regression analysis (MRA) supported by descriptive statistical analysis, classical assumption tests, and research hypothesis tests. The results of the study indicate a significant positive relationship between tax avoidance and cost of debt. In addition, when tax risk is included as a moderating variable, the relationship becomes even more positive and significant. These findings indicate that tax avoidance practices tend to increase a company's debt costs, and the accompanying tax risk amplifies this effect by increasing the health of creditors.